Heteregeneous integration on Si platfotform: emerging nanoelectronics for 'More-than-Moore' and 'Beyond CMOS approaches' - Abdul Manaf, Hashim, Engr. Assoc. Prof.; Shaharin Fadzli, Abd. Rahman, Engr.; Mastura Shafinaz, Zainal Abidin, Engr. (The Institution of Engineers, Malaysia, 2013)
Link to publisher’s homepage at http://www.myiem.org